Features of flushing an oil well - Bendag, Muad F L; Khomenko, Volodymyr (My University, 2023)
The first flushing of oil wells during drilling was carried out more than 100 years ago, when developing an oil field near the city of Grozny. Ordinary water was used as a washing liquid at that time. Currently, this technological operation is one of the main ones in the rotary drilling method. The main task of the circulation of the drilling fluid during drilling is to remove the remnants of drilled rocks, in order to avoid additional wear of the rock cutting equipment. The effectiveness of bottomhole cleaning depends on both the rate of passage of the flushing solution and its performance. That is why the flushing fluid is prepared according to established recipes and both geological (rock type, reservoir pressure, reservoir temperature, reservoir water availability, etc.) and technological factors of an oil well (depth, diameter) are necessarily taken into account during preparation.
Keywords: flushing of oil wells; промивання нафтових свердловин; rotary drilling method; роторний спосіб буріння; circulation